1998
DOI: 10.1046/j.1365-313x.1998.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Homology modelling and molecular dynamics aided analysis of ligand complexes demonstrates functional properties of lipid‐transfer proteins encoded by the barley low‐temperature‐inducible gene family, blt4

Abstract: SummaryThe homology modelling technique was used to predict the tertiary structures of three members of the lowtemperature-inducible barley vegetative shoot epidermal lipid-transfer protein (LTP) family, BLT4, on the basis of the X-ray crystallographically determined three-dimensional structure of a maize seedling LTP. Differences between the maize LTP and the BLT4 family include amino acid substitutions around the entrance and inside the predicted hydrophobic binding tunnels of these proteins. Because of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 32 publications
(64 reference statements)
3
5
0
Order By: Relevance
“…Five different LTP groups were apparent based on sequence similarity; all groups exhibited high homology to different families of barley non‐specific LTPs, recently associated with defence responses in plants (García‐Olmedo et al 1998). The blt4.9 gene in barley, homologous to clone TaLt19C10 in this study, was previously identified as low‐temperature‐responsive (Hughes et al 1992, White et al 1994, Keresztessy and Hughes 1998). LTPs in winter wheat appear to be members of a multigene family that are upregulated in a similar fashion in response to exposure to above‐zero, hardening temperatures.…”
Section: Discussionmentioning
confidence: 85%
“…Five different LTP groups were apparent based on sequence similarity; all groups exhibited high homology to different families of barley non‐specific LTPs, recently associated with defence responses in plants (García‐Olmedo et al 1998). The blt4.9 gene in barley, homologous to clone TaLt19C10 in this study, was previously identified as low‐temperature‐responsive (Hughes et al 1992, White et al 1994, Keresztessy and Hughes 1998). LTPs in winter wheat appear to be members of a multigene family that are upregulated in a similar fashion in response to exposure to above‐zero, hardening temperatures.…”
Section: Discussionmentioning
confidence: 85%
“…Knowledge of the relationship between the cavity structure and the affinity for various lipidic ligands, as well as between protein structure and membrane interaction, would help in defining the role(s) of the various isoforms of LTP. As an example, it was shown that a lowtemperature-inducible barley LTP differs in its structural and functional properties from maize LTP (49). This could be related to potential roles of LTP in frost acclimatization in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Results show that only one acyl chain of the hydrophobic tails of fatty acids is inserted in the protein internal cavity. Different conformational changes are observed after lipid binding to the different LTPs as a consequence of their different cavity size and accessibility [40,44,63,65]. A limit example of variability in the internal cavity is given by Ace-AMP1, a potent antimicrobial LTPlike protein described in onion seeds [69] and that has two tryptophan residues in its primary sequence.…”
Section: Comparison Of the Three-dimensional Structure Differences Ofmentioning
confidence: 99%